Voiler et dévoiler : temps et illusion dans Alumbramiento de Víctor Erice - Miguel Rodrigo (Cahiers de Civilisation Espagnole Contemporaine)
Since the beginning of his career, Víctor Erice's filmography has been built around two major questions: the notion of time in the cinema and the relationship between filmed image and real image, two inseparable elements in so far as any filmic image is made up, precisely, of time. In a very fertile tension, Erice's cinema integrates this reflexive dimension into stories that do not question the conventions of traditional cinema: the construction of the plot and the characters aims to recreate a "plausible" temporality, a framework more or less comparable to the daily experience that the spectator has of time. Alumbramiento, his latest film, is a particularly relevant example: organically integrated into a very classic narrative scheme, a bold reflection unfolds on the illusory nature of cinematic time while respecting the artifice that makes it possible.